A COMUNICAÇÃO MERCADOLÓGICA NA SOCIEDADE EM REDE: apropriação da cultura participativa pela publicidade - Dal, Jorge Luiz Garcia Van (2014)
The advertising market is experiencing a major transformation in a short time and has had to learn to deal with an audience that act and interact with brands, and more than a means of communication, seeking ways of relating. Becomes extremely important to reflect on the most appropriate forms of advertising that are relevant to this new scenario. This work aims to understand how advertising is appropriating the participatory culture in socio-technical context of the network society. For this method was used as the literature and case study of campaign by Stella Artois beer, called The King of Cannes. It was noticed that the said campaign reinforces participatory advertising, unlike traditional interruption-based advertising. This case exemplifies the possible changes in advertising practices that must go hand in technological expansion, the convergence of media and the relationship with the consumer public, taking into account the practical access mediated communication technologies that enable consumer relations and exchanges with organizations in the cyberspace environment.